Temperature drives variation in flying insect biomass across a German malaise trap network. Issue 2 (19th November 2021) - Welti, Ellen A. R.; Zajicek, Petr; Frenzel, Mark; Ayasse, Manfred; Bornholdt, Tim; Buse, Jörn; Classen, Alice; Dziock, Frank; Engelmann, Rolf A.; Englmeier, Jana; Fellendorf, Martin; Förschler, Marc I.; et al.
ABSTRACT: Among the many concerns for biodiversity in the Anthropocene, recent reports of flying insect loss are particularly alarming, given their importance as pollinators, pest control agents, and as a food source. Few insect monitoring programmes cover the large spatial scales required to provide more generalizable estimates of insect responses to global change drivers. We ask how climate and surrounding habitat affect flying insect biomass using data from the first year of a new monitoring network at 84 locations across Germany comprising a spatial gradient of land cover types from protected to urban and crop areas. Flying insect biomass increased linearly with temperature across Germany. However, the effect of temperature on flying insect biomass flipped to negative in the hot months of June and July when local temperatures most exceeded long‐term averages. Land cover explained little variation in insect biomass, but biomass was lowest in forests. Grasslands, pastures, and orchards harboured the highest insect biomass. The date of peak biomass was primarily driven by surrounding land cover, with grasslands especially having earlier insect biomass phenologies. Standardised, large‐scale monitoring provides key insights into the underlying processes of insect decline and is pivotal for the development of climate‐adapted strategies to promote insect diversity. In a temperate climate region, we find that the positive effects of temperature on flying insect biomass diminish in a German summer at locations where temperatures most exceeded long‐term averages. Our results highlight the importance of local adaptation in climate change‐driven impacts on insect communities. Abstract : We introduce the German Malaise Trap Program, a new Germany‐wide monitoring network of flying insects, and analyse spatial and seasonal variation in insect biomass during the first monitoring year (2019). Flying insect biomass generally increased with temperature. However, in the hottest months, at the locations where temperatures most exceeded long‐term averages, temperature had a negative effect on flying insect biomass. Grasslands, compared to forests, urban areas, or cropland, tended to support the greatest insect biomass, and had the earliest phenological peaks of flying insect biomass.